International Entrepreneurship in Emerging Markets : Nature, Drivers, Barriers and Determinants. - Haddoud, Mohamed Yacine (Contemporary Issues in Entrepreneurship Research Ser., 2019)
This volume presents insights from Brazil, China, India, Pakistan, Sri Lanka and Turkey to enlighten scholars by unearthing the nature, drivers, barriers and determinants of entrepreneurship in emerging markets.